Peningkatan Minat dan Prestasi Belajar IPS teams Achievement Divisions Di SMP - Heni Rina Setiyawati (Jurnal VARIDIKA, 2015)
This aimed of the researceh is to descript: (1) The implementation of cooperative learning model STAD in IPS learning can improve learning increase of the students in grade  VII B SMP Negeri 1 Kedawung on the second semester of academic year 2014/2015, (2) The implementation of cooperative learning model STAD in  IPS  learning can improve learning Achievement of student in grade VII B SMP Negeri 1 Kedawung on the second semester of academic year 2014/2015. This research use classroom action research method. Subjects of this research are the  students of  grade VII B SMP Negeri 1 Kedawung Sragen. Data collection technique in this research are interviews, tests, observations, and questionnaires. Mechanical checks the validity of the data by the method  triangulation techniques. Technical analysis has done by means of data collection, data reduction, data presentation, and drawing conclusions. The process of research carried out three cycles, in each cycle includes four stages of action planning, action, observation and reflection.       The results showed that: (1) The implementation of cooperative learning model STAD in IPS learning can improve learning increase student of the students in grade  VII B SMP Negeri 1 Kedawung on the second semester of academic year 2014/2015, (2) The  implementation of cooperative learning model STAD in IPS learning can improve learning Achievement of the students in grade VII B SMP Negeri 1 Kedawung on the second semester of academic year 2014/2015. The increase students learning interest can be seen from the results of student interest questionnaire after implementation of the action, in the first cycle  reaches 50%, the second cycle increased to 68.75%, and the third cycle increased to 87.50 %. While student achievement on initial conditions shows that the average value of 68.28 with classsical completeness of  53.12%, after the action on the first cycle increased the average value becomes 74.53 with classical completeness of 65.62%, second cycle increased with an average value of 76.56 with classical completeness of 78%, and the third cycle has increased again, with an average value of 81.56 reached with classical completeness reached 87.5